2023
DOI: 10.3311/ppci.21260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Cyclic Behavior of the Sloped Extended End-plate Beam-to-column Connections

Abstract: In the Northridge and Kobe earthquakes, brittle failure of the welded beam-to-column connections was observed in steel structures. So, bolted connections were considered as an alternative to these kinds of connections. Extended end-plate beam-to-column con-nection is one of the most commonly used connections in steel structure. In this article, the behavior of the sloped extended end-plate beam-to-column connections is studied. Finite element method was used to investigate the behavior of the connection by ABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It resulted in minimal damage, making it a promising option for future designs. Miryahyavi et al (2023) studied the cyclic behavior of sloped extended end-plate beam-to-column connections using Finite Element Method. Results showed that increasing beam angle decreased ductility and moment-resisting capacity but the models satisfied design code limitations.…”
Section: Introductionmentioning
confidence: 99%
“…It resulted in minimal damage, making it a promising option for future designs. Miryahyavi et al (2023) studied the cyclic behavior of sloped extended end-plate beam-to-column connections using Finite Element Method. Results showed that increasing beam angle decreased ductility and moment-resisting capacity but the models satisfied design code limitations.…”
Section: Introductionmentioning
confidence: 99%